Factors associated with residual neuromuscular blockade with rocuronium after laparoscopic abdominal surgery (TẠP CHÍ Y DƯỢC THÁI BÌNH, 2024)
Objective: Residual neuromuscular blockade commonly occurs after laparoscopic abdominal surgery, impacting patient recovery and safety. This study aimed to identify factors associated with residual neuromuscular blockade when using rocuronium in laparoscopic procedures.Method: The researchers conducted a cross-sectional descriptive study on 92 patients undergoing laparoscopic surgery in the Department of Anesthesia and Resuscitation, Nguyen Tri Phuong Hospital. The residual neuromuscular blockade was monitored using the TOF (train of four) index with the TOF-watch nerve stimulator, a device used to monitor neuromuscular function, was applied at the time of extubation.Results: The incidence of residual neuromuscular blockade with rocuronium (TOF < 0.9) at the time of extubation following laparoscopic abdominal surgery was 53.3%, patients who did not receive prophylactic antibiotics had a higher rate of residual neuromuscular blockade compared to those who did (p